Melacak Akar Radikalisme Islam di Indonesia - Ahmad Rizky Mardhatillah Umar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2010)
Radicalism nowadays becomes a popular discourse in Indonesia. The fall of Soeharto in 1998 was also followed by the rise of some groups which enroots their ideology and value with the ideology of Islamic political movement in Middle East. Many authors even connect this phenomenon to terrorism. By those points of view, they try to encounter terrorism by de-radicalizing people and promoting the empowerment of moderate society. But this point of view is argued by some authors who think that terrorism differs from radicalism. It is structural problem –poverty, oppression, political authoritarianism— which implies violence and terror. It leads us to a question: What cause radicalism? This article attempts to analyze the historical and political-economic root of Radical Islam group in Indonesia. By analyzing those problems, we will elaborate the problem of Islamic radicalism in structural perspective of post-New Order Indonesia.